Analisis Pengaruh Persepsi Kemudahan Penggunaan dan Persepsi Manfaat terhadap Minat Beli dengan Kepercayaan Sebagai Variabel Intervening (Studi pada Pengunjung Toko Online berrybenka.com di Kalangan Mahasiswa Universitas Diponegoro) - Faradila, Rr. Selli Nisrina; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to analyze the influence of perceived ease of use and perceived usefulness on purchase intention using trust as mediator study case on online store berrybenka.com. This study used two independent variables that are perceived ease of use and perceived usefulness, purchase intention variable as a dependent variable and trust variable as an intervening variable. Simple random sampling method is used for this research. Sample were collected from 150 respondents who ever had used berrybenka.com website. Multiple regression analysis is used for this study. The results showed that perceived ease of use have positive and significant effect on trust, perceived usefulness have positive and significant effect on trust and perceived ease of use, perceived usefulness, and trust have positive and significant effect on purchase intention.